The implications of process writing assessment on scores, quality and revisions of second draft for grade five and seven students - Salhab, Abeer Ali. (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of English, 2012)
This study examines the effect of extended time on the scores and quality of revised drafts of 112 ESL grade five and seven students during writing assessment. It was carried out in one of Beirut schools in Lebanon. Instead of one-draft timed essay written in a 50- minute session, the participants were given an additional period to receive constructive peer feedback in order to improve the quality of their essays. Giving students extra time and making them use the process writing revising skills in an assessment context didn t result in high outcomes though less proficient writers improved the quality of their essays and gained some cognitive and social skills. Statistical analysis including descriptives, t-tests, Chi-square test, multiple regression, and MANOVA showed a significant difference in the means of scores of all participants between the first and the revised drafts. Grade five participants showed higher increase of scores in the second drafts. Students of both grades devoted most of their time for substitutions, then additions and spellings. Male revisions were higher than females' and scored better on the revised drafts. Most substantive revisions were made by the low and mid-low achievers; their score on the revised drafts was mostly deferring from the mid-high and high achievers based on ideas, fluency and conventions. Certain pre-steps and procedures are necessary before the implementation of this writing assessment method in the future.
: Mémoire
Keywords: Basic Education English Language Education School Evaluation; Enseignement de base L enseignement de la Langue Anglaise Evaluation Scolaire